2020
DOI: 10.1039/c9ra09999a
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous removal of multiple heavy metals from soil by washing with citric acid and ferric chloride

Abstract: Citric acid and ferric chloride exhibited synergistic effect on the removal of multiple heavy metals from soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…The effiencies were in the sequence of FeCl3 > EDTA > HCl which is similar to data reported in literature [42,43]. The removal efficiencies were observed slightly lower than the reported data [43,44]. This may be due to the presence of more clay fraction in the soil studied.…”
Section: Column Leaching Tests and Analytical Methodssupporting
confidence: 89%
“…The effiencies were in the sequence of FeCl3 > EDTA > HCl which is similar to data reported in literature [42,43]. The removal efficiencies were observed slightly lower than the reported data [43,44]. This may be due to the presence of more clay fraction in the soil studied.…”
Section: Column Leaching Tests and Analytical Methodssupporting
confidence: 89%
“…In contrast, organic acids, with a lesser environmental impact, have also shown excellent performance with respect to the removal of heavy metals from soils or ash. Specifically, Hong et al reported that more than 70% of Pb and Cd can be removed using 0.1 M ethylenediaminetetraacetic acid (EDTA) solution and citric acid (CA), while Shi et al reported soil Cd and Pb removal rates of 73.1 and 98.0%, respectively 37 , 38 . It has also been reported that oxalic acid (OA) is effective in the removal of As, showing a removal efficiency of more than 50% for As 39 .…”
Section: Introductionmentioning
confidence: 99%
“…In most studies in which different agents have been used to realize heavy metal removal, the focus has always been on the application of single-agent solutions. However, the various agents studied to date show different removal efficiencies for different heavy metals 35 38 , 45 . This implies that effectively realizing the removal of multiple heavy metals using a single-agent solution remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing industrial Cd discharges originating primarily from metal mining, refining, smelting, metal plating, electrolysis, electroplating, and other industries have deteriorated the aqueous environment [3]. Due to its non-biodegradable nature, Cd can accumulate in the environment and food chain; thus, it has adverse effects on ecosystems and human safety [4]. Therefore, Cd contamination has drawn an increasing amount of concern around the world.…”
Section: Introductionmentioning
confidence: 99%